2016
DOI: 10.3390/molecules21060724
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic, X-ray Diffraction and DFT Studies of Novel Benzimidazole Fused-1,4-Oxazepines

Abstract: A series of benzimidazole-tethered oxazepine heterocyclic hybrids has been synthesized in good to excellent yields from an N-alkylated benzimidazole 2-carboxaldehyde, which in turn was accomplished from o-phenylenediamine in three good yielding steps. The calculated molecular structure of compounds 2-methyl-4-(2-((phenylimino)methyl)-1H-benzo-[d]imidazol-1-yl)-butan-2-ol 9 and 10 3,3-dimethyl-N-phenyl-1,2,3,5-tetrahydrobenzo- [4,5]imidazo[2,1-c][1,4]oxazepin-5-amine using the B3LYP/6-31 G(d, p) method were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…InCl 3 -catalyzed the synthesis of benzimidazole-fused 1,4-oxazepines by intramolecular addition of a pendant alcohol onto an in situ-generated imine ( Scheme 26 ) [ 87 ].…”
Section: Syntheses Of Ring-fused Benzimidazoles and Imidazobenzimidazolesmentioning
confidence: 99%
“…InCl 3 -catalyzed the synthesis of benzimidazole-fused 1,4-oxazepines by intramolecular addition of a pendant alcohol onto an in situ-generated imine ( Scheme 26 ) [ 87 ].…”
Section: Syntheses Of Ring-fused Benzimidazoles and Imidazobenzimidazolesmentioning
confidence: 99%
“…The effects of the molecular structure on chemical reactivity have been studied extensively [5357]. Quantum chemical indices calculated to predict that a compound is fitted to be a corrosion inhibitor are: energy of the highest occupied molecular orbital (E HOMO ), energy of the lowest unoccupied molecular orbital (E LUMO ), dipole moment (μ), polarizability (α), total natural charges (Q total ), total Mulliken charges (Z total ), adiabatic ionization potential (I a ), adiabatic electron affinity (A a ), Molar volume (V i ), aromaticity-magnetism based on Nuclear Independent Chemical Shift (NICS), the number of electrons transferred (ΔN) and electrophilicity index (ω a ) [52, 5871]. The radial distribution function (RDF) study confirmed that both the neutral and protonated form of the inhibitor show significant interaction with the steel surface.…”
Section: Benzimidazoles As Corrosion Inhibitors For Other Metalsmentioning
confidence: 99%
“…It is hypothesized that the reaction of oxazole 21 with Grignard or organolithium reagent produced an inactive dianion by deprotonation of both the indole NH and the active methylene group. Water addition to, or epoxidation of, the isopropylidene double bond in labradorin 5 (22) was unsuccessful with various reagents, such as H 2 SO 4 /H 2 O at room temperature, 17 polyphosphoric acid (PPA) at 90 °C, 18 Hg(OAc) 2 /THF-H 2 O then NaOH/NaBH 4 , 19 HCl/THF-H 2 O at reflux, 20 and meta-chloroperoxybenzoic acid (mCPBA) at 0 °C. 21 Finally, upon treatment of labradorin 5 (22) with 50% aqueous H 2 SO 4 in boiling 1,4-dioxane 22 for 4 days, pimprinol B (2) was produced with 15% conversion and in 11% isolated yield.…”
Section: Paper Syn Openmentioning
confidence: 99%